Pengaruh Pelatihan Differentiated Instruction Terhadap Peningkatan Kompetensi Mengajar Guru Madrasah Ibtidaiyah Dalam Pembelajaran Berbasis Keberagaman Siswa - Aqodiah; Baiq Ida Astini; Khairunnisa (STAI AL-AMIN, 2026)
This study aims to analyze the effect of Differentiated Instruction training on improving the teaching competence of Madrasah Ibtidaiyah teachers in diversity-based learning environments. The research employed a quantitative approach with a quasi-experimental design involving experimental and control groups. The subjects consisted of Madrasah Ibtidaiyah teachers who participated in a Differentiated Instruction training program. Data were collected through observation and questionnaire instruments measuring teachers’ pedagogical and professional competencies before and after the training. Data analysis was conducted using inferential statistical tests to identify significant differences between the two groups. The findings indicate that Differentiated Instruction training has a positive and significant effect on enhancing teachers’ teaching competence, particularly in designing adaptive learning, managing heterogeneous classrooms, and adjusting instructional strategies to meet individual student needs. These results confirm that differentiation-based training is an effective intervention for improving the quality of teaching practices in Madrasah Ibtidaiyah. In conclusion, the systematic implementation of Differentiated Instruction training can serve as a strategic approach for teacher professional development and for improving the quality of Islamic primary education that is responsive to student diversity.